Systems Analysis of Insulin and IGF1 Receptors Networks in Breast Cancer Cells Identifies Commonalities and Divergences in Expression Patterns - Sarfstein, Rive; Yeheskel, Adva; Sinai-Livne, Tali; Pasmanik-Chor, Metsada; Werner, Haim (Frontiers in Endocrinology, 2020)
Insulin and insulin-like growth factor-1 (IGF1), acting respectively via the insulin (INSR) and IGF1 (IGF1R) receptors, play key developmental and metabolic roles throughout life. In addition, both signaling pathways fulfill important roles in cancer initiation and progression. The inherent complexity of the INSR/IGF1R pathways, along with the well documented cross-talk between insulin-like ligands and receptors, translated into a disappointingly slow pace in the development of INSR/IGF1R-directed therapies in oncology. The present study was aimed at identifying mechanistic differences between INSR and IGF1R using a recently developed bioinformatics tool, the Biological Network Simulator (BioNSi). This application allows to import and merge multiple pathways and interaction information from the KEGG database into a single network representation. The BioNsi network simulation tool allowed us to exploit the availability of gene expression data derived from breast cancer cell lines with specific disruptions of the INSR or IGF1R genes in order to investigate potential differences in protein expression that might be linked to biological attributes of the specific receptor networks. Modeling-generated information was corroborated by experimental and biological assays. Our simulation analysis identified a number of commonalities and, most importantly, dissimilarities between the IGF1R and INSR pathways that were experimentally validated and that might help explain the basis for the biological differences between these networks.